Penanggulangan Genangan Air dan Peningkatan Volume Air Tanah Melalui Sumur Resapan Air Hujan Di Daerah Semi-Arid Kota Kupang - Ketut M. Kuswara; Hikmah Hikmah; Roly Edyan; Aldino Arfaksad Taopan (Varied Knowledge Journal, 2026)
Urban areas with semi-arid climates such as Kupang City face the problem of waterlogging in the rainy season and a shortage of groundwater in the dry season. One area that frequently experiences inundation is RT 15/RW 06, Oesapa Subdistrict due to high surface runoff, changes in land use, and a drainage system that is not functioning optimally. This research aims to analyze the existing conditions of the area, calculate the amount of rainwater runoff discharge, and design a model and capacity of infiltration wells as an effort to overcome inundation and increase the volume of groundwater. The research method used is a quantitative descriptive method with hydrological analysis using rainfall data, runoff discharge calculations, and technical design of infiltration wells. The research results show that the rainwater runoff discharge in the research area is quite large and cannot be accommodated by the existing drainage system. Implementing infiltration wells with appropriate designs can reduce waterlogging while increasing the potential for groundwater replenishment. It is hoped that this research can become a reference in environmentally sound rainwater management in semi-arid urban areas.